William H. Bridges (Editor), Digest of the Charters and Ordinances of the City of Memphis, from 1826 to 1867, Inclusive, Together with the Acts of the Legislature Relating to the City, with an Appendix, 44 (1867), §§ 4746, 4747, 4753, 4757 - (:unkn) unknown (General Publisher, 1867)
Prohibited the carrying of a concealed Bowie knife, Arkansas tooth pick, dirk, sword cane, Spanish stiletto, belt or pocket pistol, or other knife or weapon. Also prohibited selling such a weapon or using such a weapon to threaten people.
--
Keywords: CARRY - CONCEALED